Takhrij and Syarah Hadith of Chemistry: Study of the Prohibition of Blowing Food and Drink in a Scientific Perspective - Kevin Mardiansyah Bayu Ardana; Hanipatudiniah Madani; Taufik Rahman; Ira Ryski Wahyuni; Deni Miharja (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad regarding the prohibition of blowing food and drinks. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this research are proof of the hadith about blowing hot drinks from a scientific perspective. The conclusion of this research is that the takhrij and syarah hadith of the Prophet SAW regarding the prohibition of blowing food and drinks by chemical analysis are proven true that blowing food and drinks is harmful to the body.